India’s Nepal Policy (1950-2020) and Globalisation in Nepal: Challenges within and from China (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Seventy years (1950-2020) of India’s diplomatic ties with Nepal have been defined by deep-rooted socio-cultural, economic and people to people relations. The two countries share an open border that is nowhere found in a contested South Asia. Meanwhile, as a landlocked country between India and China, Nepal has struggled to keep up with its national interests and global aspirations. With its India centric foreign policy, Nepal has time and again attempted to reduce its dependence on India and sought to improve ties with China and other countries. The advent of globalisation in the 1990s bestowed Nepal to explore opportunities for its economic growth and shift to remuneration and services-based economy from agriculture. The labour migration from Nepal to third countries changed Nepal’s foreign policy objectives with India as until now India was the largest recipient of the Nepalese labourers. The arrival of democracy allowed Nepal to interact with China more openly in the last two decades, which has stood as a challenge to India’s traditional presence in Nepal. In this light, the present study examines the seventy years of India’s Nepal policy and attempts to contextualise China into it. It studies the overriding elements of Nepal’s foreign policy, along with India and China’s strategic interests in Nepal. With a focus on India’s Nepal policy, the paper further argues that India’s missteps and assertive stance towards Nepal have caused a great deal of damage, eventually pushing Nepal towards China. These moves have also presented Beijing an opportunity to advance its ties in trade, investment and military relations with Nepal and ensure stability and control in Tibet by putting a stop to anti-China activities in Nepal with the help and support from the Nepalese Government and Army.
Keywords: India’s Nepal Policy; Neighbourhood First; Blockade; China; Tibet